2008
DOI: 10.1021/bp070178q
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of Four-Helix Bundle Proteins That Bind Nonbiological Cofactors

Abstract: Recent work is discussed concerning the computational design of four-helix bundle proteins that form complexes with nonbiological cofactors. Given that often there are no suitable natural proteins to provide starting points in the creation of such nonbiological systems, computational design is well suited for the design and study of new protein-cofactor complexes. Recent design efforts are presented in the context of prior work on the de novo design and engineering of porphyrin-binding four-helix bundle protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…Although a detailed understanding of protein folding, evolution, and design remains elusive, it is generally acknowledged that gene duplication and fusion is the likely evolutionary process responsible for the emergence of common symmetric protein architecture from simpler peptide motifs (McLachlan, 1972;Ohno, 1970). Symmetry is also a strategy to substantially simplify and parameterize computational methods for efficient de novo protein design (Bellesia et al, 2010;Fortenberry et al, 2011;Kuhlman et al, 2003;Lehmann and Saven, 2008;Richter et al, 2010) and exact symmetry of protein primary and tertiary structure has been experimentally shown to confer robust foldability in the face of major structural rearrangements (Longo et al, 2013). Despite the prevalence of symmetry in protein tertiary structure, a clear understanding of the role of symmetry in protein evolution, as well as the development of practical symmetric design principles (e.g., principles that can leverage the simplifying power of symmetry with the nucleation condensation mechanism of protein folding) are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Although a detailed understanding of protein folding, evolution, and design remains elusive, it is generally acknowledged that gene duplication and fusion is the likely evolutionary process responsible for the emergence of common symmetric protein architecture from simpler peptide motifs (McLachlan, 1972;Ohno, 1970). Symmetry is also a strategy to substantially simplify and parameterize computational methods for efficient de novo protein design (Bellesia et al, 2010;Fortenberry et al, 2011;Kuhlman et al, 2003;Lehmann and Saven, 2008;Richter et al, 2010) and exact symmetry of protein primary and tertiary structure has been experimentally shown to confer robust foldability in the face of major structural rearrangements (Longo et al, 2013). Despite the prevalence of symmetry in protein tertiary structure, a clear understanding of the role of symmetry in protein evolution, as well as the development of practical symmetric design principles (e.g., principles that can leverage the simplifying power of symmetry with the nucleation condensation mechanism of protein folding) are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Much exciting progress is being made in this de novo design of heme proteins at present 14–20. Heme proteins are being developed as novel biomolecular with non‐linear optical properties, as molecules that self‐assemble at an interface providing an ordered material with electron transfer properties, and as “smart” materials that respond to stimuli such as changes in pH, ionic strength or redox environment 21–29. The design and development of such heme proteins with specific structural and functional properties requires a firm understanding of the heme group and its binding sites in proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The main structural models used to study the packing effects following fluorination were 4‐helix bundles. This 3‐D arrangement is commonly present in proteins and it has been the topic of extensive de novo design efforts . It has been demonstrated that the hydrophobic core of a 4‐helix bundle can be built from contact interactions between hydrophobic residues at the “a” and “d” positions of a helical heptad (abcdefg) n repeat.…”
Section: Effect Of Fluorination On Enzymatic Stability and Reactivitymentioning
confidence: 99%